PENGARUH PENAMBAHAN LIMBAH PLASTIK POLYPROPYLENE (PP) TERHADAP KETAHANAN RAVELLING CAMPURAN ASPHALT CONCRETE WEARING COURSE - Hery Awan Susanto; Karina Merdiana; Eva Wahyu Indriyati (Direktorat Bina Teknik Jalan dan Jembatan, 2021)
Ravelling is road damage that occurs when the bond between aggregate and asphalt has been lost. One of the factors of ravelling damage is caused by the decreasing value of cohesion and adhesion. Therefore, the material factor becomes one of the parameters in increasing the value of cohesion and adhesion to asphalt. To improve material quality as well as an effort to reduce environmental pollution, polypropylene (PP) plastic waste is used in asphalt concrete wearing course mixtures. This study aims to determine the effect of adding polypropylene (PP) plastic waste to Marshall characteristics and revelling resistance seen from the VIM value and abrasion value with variations in polypropylene (PP) waste content as much as 0%, 2%, 4%, and 6% of the weight of the asphalt. Marshall test results show that the values ​​of stability, VMA, and MQ tend to increase, while the values ​​of flow, VIM and VFA tend to decrease with the increase in the percentage of polypropylene (PP) plastic waste content in the asphalt. As for the reMults of the abrasion value with a simple ravelling modification tool, it shows that the higher the percentage of polypropylene (PP) plastic waste in the asphalt, the smaller the VIM and abrasion value. It can be concluded that the addition of polypropylene (PP) plastic waste can improve the performance of the mixture against ravelling resistance seen from the VIM value on the Marshall parameter and the abrasion value of the ravelling test.